Pemanfaatan Rizobakteri Penghasil Acetoin Sebagai Biofertilizer Untuk Memacu Pertumbuhan dan Hasil Tanaman Padi (Oryza Sativa L.) - adrianus aris; gardis andari (Universitas Musamus, Merauke, Papua, 2020)
This study aims to look at the application of acetoin-producing rizobacteria as biofertilizers for boosting the growth of rice plants in dissolving phosphates and fixing nitrogen. The experimental design used was a randomized block design (RBD), consisting of 6 (six) treatments, 4 (four) treatments with rizobacteria isolates (Rg21 isolates, Pd13 isolates, Pd7 isolates, and Bb7 isolates), one treatment with synthetic acetoin, and one control. Each treatment was repeated 4 (four) times so that there were 24 experimental units consisting of 10 pots of rice plants. The size of the pot used is a surface diameter of 30 cm, filled with growth media in the form of a layer of paddy soil (taken to a depth of 20 cm from the soil surface) and compost with a ratio of 3: 1. The results showed that the treatment of rhizobacteria producing acetoin was able to spur the growth of rice plants by dissolving phosphates that were still bound by colloidal soil so that it was not available for plants to become available P. Likewise, rhizobacterial treatment is able to fix Nitrogen by changing enzymatically organic N compounds into ammonium